Synthesis, Characterization, and Evaluation of a Hindered Phenol-Linked Benzophenone Hybrid Compound as a Potential Polymer Anti-Aging Agent - Shenshuai Wang; Yingjie Huang; Weiye Sun; Xufeng Lin (MDPI AG, 2024)
Hindered phenol antioxidants and benzophenone UV absorbers are common polymer additives and often used in combination applications to enhance the anti-aging performance of polymer materials. This study primarily aims to incorporate hindered phenol and benzophenone structures into a single molecule to develop a multifunctional polymer additive with good anti-aging performance. Thus, a novel potential polymer anti-aging agent, namely 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid 3-(4-benzoyl-3-hydroxyphenoxy)propyl ester (3C), was synthesized using 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid, 3-bromo-1-propanol, and 2,4-dihydroxybenzophenone as raw materials by two-step procedure. The structure of compound 3C was characterized by nuclear magnetic resonance (NMR), high-resolution mass spectrometry (HRMS), Fourier-transform infrared (FT-IR) spectroscopy, and X-ray single crystal diffraction. Its thermal stability and UV resistance were assessed using thermogravimetric analysis (TGA) and UV absorption spectroscopy (UV). The compound 3C as an additive was incorporated into the preparation of polyolefin elastomer (POE) films. The anti-aging performance of POE films was evaluated by measuring parameters such as oxidation induction time, melt flow index, transmittance, and infrared spectra of the artificially aged POE films. The results indicate that the compound 3C exhibits a promising anti-aging performance in both thermo-oxidative aging and ultraviolet aging tests of POE films and is a potential polymer anti-aging agent.